Professional Competence of Extension Personnel in Karnataka State of India (Indian Journal of Extension Education, 2023)
The study examines the level of professional competence among agricultural extension personnel in the Karnataka state of India. The study population was composed of agricultural extension personnel in development departments and Krishi Vigyan Kendra’s (Farm science center). During 2021-2022, 285 extension personnel completed self administered surveys. The design for the data collection instrument was based on a literature review and focus group recommendations. The findings showed that respondents thought they were highly competent in the areas of program evaluation, organizational skills, human relations skills, and communication skills and moderately competent in the areas of knowledge, administration, teamwork, leadership, program planning, and implementation. Respondents’ competency differed by their cadre also; ADAs, ADHs, and SMSs had high competence levels than their counterparts- AOs, AAOs, and AHOs. The findings imply that there is a need for in-service training of extension professionals in all core competency areas. Pre-service extension education curricula need to be reviewed and updated, incorporating the core competencies highlighted in the study.